Zanikanie instytucji tutela mulierum w prawie rzymskim - Zabłocka, Maria (Prawo Kanoniczne, 1987)
The first symptom of the decline of the institution of tutela mulierum was tutoris optio. Since Augustus women possessing three children were free from tutela (G. I. 145, 194). However at was only Claudius’ activity — mainly as the result of lex Claudia (G. I. 147, 171), but also due to the extension of the privilege ins trium liberorum (Svet. Claud. 18.2.—19), as well as due to SC an the strength of which in case of tutor’s absence it was possible to appoint another one (G. I. 173) — that caused a complete obsolescence of tutela mulierum in relation to freeborn women. Tutela mulierum in the days of Gaius was kept only in relation to freed women.